PRODUCTION OF MALTOOLIGOSACCHARIDES FROM HUTAN JATI VARIETY CULTIVAR TACCA (Tacca leontopetaloides) STARCH - Yopi Yopi; Nanik Rahmani; Feby Heryani Putri; Andri Fadillah Martin (SEAMEO BIOTROP, 2019)
This research aimed to extract and characterize the physicochemical properties of starch from Tacca tuber, to determine the optimum conditions for enzymatic hydrolysis to produce maltooligosaccharides, and to analyze the character of these maltooligosaccharides. The analysis was conducted by calculating the amount of reducing sugar, total sugar, and the degree of polymerization, and by using the TLC (Thin Layer Chromatography) and HPLC (High-Performance Liquid Chromatography) analyses. The Hutan Jati variety cultivar of Tacca was selected from three Tacca variety cultivars (Hutan Jati, Pulau Katang, and Gunung Batur) to produce maltooligosaccharides by enzymatic hydrolysis of crude Bacillus sp. α-amylase. The optimum conditions for the enzymatic hydrolysis of Hutan Jati variety cultivar Tacca starch for the production of maltooligosaccharides were obtained at a substrate concentration of 3% (w/v) and a ratio of enzyme and substrate at 6 hours incubation time. From 250 mL of fresh hydrolysate, 34.49 grams of powdered maltooligosaccharide were produced. The TLC and HPLC results showed a similar yield of both the liquid and powdered maltooligosaccharides with maltose, maltotriose, and maltotetraose as the main products. Considering its physicochemical characteristics and the product of its maltooligosaccharides, the starch from the tuber of Hutan Jati variety cultivar Tacca possessed strong potential for the future production of maltooligosaccharides, particularly maltotriose and maltotetraose, in food industries.